TAHAP PERKEMBANGAN MORAL ANAK PERSPEKTIF PSIKOLOGI PENDIDIKAN ISLAM - Darmalinda; Fitriani, Wahidah (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
This research examines the stages of moral development in children from the perspective of Islamic educational psychology. The main issues discussed include the linguistic definition of morality and definitions by experts. Furthermore, the research addresses the stages of moral development in children and the factors influencing their moral development. The research aims to understand how Islamic educational psychology views the moral development of children and to identify key factors contributing to the formation of moral values in this context. The research employs a qualitative approach through literature review and document analysis. Data sources are drawn from relevant books and online journals related to the stages of moral development in children within the framework of Islamic educational psychology. Data analysis involves detailing the definition of morality, describing the stages of moral development, and analyzing the factors influencing children's moral development. The results of the study indicate that Islamic educational psychology significantly contributes to understanding and shaping the moral development of children. The stages of moral development in children can be systematically categorized, and factors such as the environment, family education, and religious influence play crucial roles in this process. It is hoped that this research provides valuable insights for educators, parents, and researchers in developing holistic and morally oriented educational approaches for children.